2017
DOI: 10.1002/2016ja023538
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ripple structures revealed in OH airglow images

Abstract: Small‐scale ripple structures observed in OH airglow images are most likely induced by either dynamic instability due to large wind shear or convective instability due to superadiabatic lapse rate. Using the data set taken in the mesopause region with an OH all‐sky imager at Yucca Ridge Field Station, Colorado (40.7°N, 104.9°W), from September 2003 to December 2005, we study the characteristics and seasonal variations of ripple structures. By analyzing the simultaneous background wind and temperature observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…However, it has been reported that ripples can be rotated by the background wind and that ripples may even be created by a combination of both dynamical and convective instability (Fritts et al, 1996;Hecht, 2004). Li et al (2017) report that ripples are hard to distinguish from small-scale gravity waves. Height-resolved measurements of the horizontal wind would be needed to determine the local wind shear and make a profound statement about atmospheric instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that ripples can be rotated by the background wind and that ripples may even be created by a combination of both dynamical and convective instability (Fritts et al, 1996;Hecht, 2004). Li et al (2017) report that ripples are hard to distinguish from small-scale gravity waves. Height-resolved measurements of the horizontal wind would be needed to determine the local wind shear and make a profound statement about atmospheric instability.…”
Section: Discussionmentioning
confidence: 99%
“…Gravity wave instability can also be of convective nature when growing wave amplitudes lead to a superadiabatic lapse rate (Fritts & Alexander, 2003). In general, atmospheric instabilities like KHIs often manifest as so-called ripples -periodic structures with small spatial dimensions and short lifetimes (Peterson, 1979;Adams et al, 1988;Taylor & Hapgood, 1990;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“….". Li et al (2017) report that less than half of the ripples examined moved with the background wind, and were in fact real wave structures that are difficult to distinguish from real instability features.…”
mentioning
confidence: 93%
“…A really useful reference on this point is the recent paper by Li et al (2017), in which the authors study statistically the relation between ripples and the background atmosphere. Some of the statements made in the current manuscript are not supported in the work by Li et al (2017), e.g., line 30 on page 11 states (referring to ripples) "They move with the background wind . .…”
mentioning
confidence: 99%
See 1 more Smart Citation